Differentiated instruction based on the PBL model to improve junior high school students’ learning outcomes - Kusuma, Lola; Suanto, Elfis; Yuanita, Putri (Jurnal Gantang, 2026)
This study was conducted to improve the learning process and enhance the mathematics learning outcomes of Grade IX. A student at SMP Negeri 2 Kampar Kiri Hilir. The research was motivated by the low attainment of KKTP standards, as most students had not yet met the school's minimum score. To address this issue, differentiated instruction combined with the Problem-Based Learning (PBL) model was implemented. This approach allows students to learn at their individual readiness levels and solve contextual problems. The study employed a Classroom Action Research (CAR) design consisting of two cycles, each including the stages of planning, implementation, observation, and reflection. During the learning process, students were grouped by readiness level and actively participated in discussions. The findings revealed an improvement in the learning process, as evidenced by increased student engagement in discussions and improved learning outcomes, rising from 35% at baseline to 40% in Cycle I and 60% in Cycle II. These results indicate that differentiated instruction based on the PBL model can serve as an effective alternative for improving students' mathematics learning outcomes.